A Global Crisis of Liberal Democracy?: On Autocratic Democracy, Populism and Post-Truth Politics. Issue 1 (February 2022) - Owen, David
Abstract : This article proposes that autocratic democracy represents the natural political form of right-wing populism. It argues that while the emergence of autocratic democracy as a genuine political alternative to liberal democracy may be currently located primarily in states where liberal democratic norms were not well-consolidated, there are reasons to hold that structural features of contemporary politics in consolidated democracies relating to the decline of mass parties and the globalisation trilemma create the space for the right-wing mobilisation of populism. It is further claimed that the dilemmas of the EU in conjunction with the politics of immigration and multiculturalism provide resources for the right-wing mobilisation of populist discontents such that we should not be sanguine about the ability of liberal democracy to be resilient in the face of continuing populist pressures.